UK Consumers' Habits - Ryan Banerjee; Nicoletta Batini (Bank of England, External Monetary Policy Committee Unit, 2003)
We follow Fuhrer (2000) in estimating via Maximum Likelihood a log-linear consumption function on UK data. In doing so we consider various habit formation assumptions. We show that a model of purely "external" habits as in Fuhrer (2000) fits the UK data remarkably well, and possibly in a superior way than US data where, according to our estimates, consumers' habits look more "internal" in that they appear indexed to past average consumption of only a subset of (peer) consumers in the economy, rather than total past per capita consumption. We also find that for about one seventh of UK consumers, current consumption equals current income_a strong violation of the permanent income hypothesis. Embedded in a sticky price-sticky inflation open-economy monetary model, the model that we estimate helps mimic the hump-shaped response of the output gap to income and interest rate shocks observed in the UK. Estimates of output Euler equations for the UK using a similar method agree with our general results. The consumption and output models that we estimate forecast significantly better than unrestricted open-economy VARs.
Keywords: 330